2018
DOI: 10.3390/pr6050049
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Joint Dip Angle on the Mechanical Behavior of Infilled Jointed Rock Masses under Uniaxial and Biaxial Compressions

Abstract: Due to the complex formation process of a rock mass, a large number of fissures, joints, faults, other defects exist and the defects commonly contain infilled materials. The jointed rock masses are in a complex geological environment, in which the geometric distribution and the boundary condition can greatly affect the mechanical behavior of the infilled jointed rock mass. In this study, the infilled jointed rock mass specimens with different dip angles are prepared using similar materials, and the uniaxial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 24 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…However, the influence of transverse joints was also not considered in their study. Han et al (2018) investigated the failure mechanism of intermittent jointed rock masses subjected to biaxial compression by physical tests. However, they did not consider the continuous joints perpendicular to the intermittent joints.…”
Section: Influence Of Transverse Joints On Anisotropy and Shape Effec...mentioning
confidence: 99%
“…However, the influence of transverse joints was also not considered in their study. Han et al (2018) investigated the failure mechanism of intermittent jointed rock masses subjected to biaxial compression by physical tests. However, they did not consider the continuous joints perpendicular to the intermittent joints.…”
Section: Influence Of Transverse Joints On Anisotropy and Shape Effec...mentioning
confidence: 99%
“…Among them, joint cracks are the most widely distributed structural plane in rock masses [1]. The existence of joints in a rock mass seriously affects the mechanical properties of the rock mass, the smooth blasting forming effect, and the stability of the surrounding rock after blasting, among which the joint angle has the greatest influence on the smooth blasting forming effect of roadways [2,3]. Therefore, this paper takes the joint angle as the starting point to study the expansion of explosive cracks in rock masses under different joint angles and the stress variation of rock mass elements, and it summarizes the specific influence of different joint angles on the smooth blasting of roadways to provide guidance for practical engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al [16] conducted direct shear tests on sandstone samples grouted with cement to study the influence of the filling ratio on the shear strength and failure behavior. Han et al [17] carried out uniaxial and biaxial compressive tests on the rock-like specimens with grout-infilled flaws having different flaw dip angles and found that the failure modes for uniaxial compressive tests are different to those for biaxial compressive tests. Experimental and numerical methods were followed by Chang et al [18] to investigate the strength and crack behavior of rock samples with a filled fissure under uniaxial compression, and their results show that, if the filling strength is lower than the critical value, secondary cracks disappear as the filling strength increases; however, if the filling strength is larger than the critical value, cracking behaviors are not affected by the filled flaw.…”
Section: Introductionmentioning
confidence: 99%